Controlabilidade para alguns modelos da mecânica dos fluidos - Souza, Diego Araújo de (2014)
The aim of this thesis is to present some controllability results for some fluid mechanic models. More precisely, we will prove the existence of controls that steer the solution of our system from a prescribed initial state to a desired final state at a given positive time. The two first Chapters deal with the controllability of the Burgers-α and Leray-α models. The Leray-α model is a regularized variant of the Navier-Stokes system (α is a small positive parameter), that can also be viewed as a model for turbulent flows; the Burgers-α model can be viewed as a related toy model of Leray-α. We prove that the Leray-α and Burgers-α models are locally null controllable, with controls uniformly bounded in α. We also prove that, if the initial data are sufficiently small, the pair state-control (that steers the solution to zero) for the Leray-α system (resp. the Burgers-α system) converges as α → 0+ to a pair state-control(that steers the solution to zero) for the Navier-Stokes equations (resp. the Burgers equation). The third Chapter is devoted to the boundary controllability of inviscid incompressible fluids for which thermal effects are important. They will be modeled through the so called Boussinesq approximation. In the zero heat diffusion case, by adapting and extending some ideas from J.-M. Coron [14] and O. Glass [45], we establish the simultaneous global exact controllability of the velocity field and the temperature for 2D and 3D flows. When the heat diffusion coefficient is positive, we present some additional results concerning exact controllability for the velocity field and local null controllability of the temperature. In the last Chapter, we prove the local exact controllability to the trajectories for a coupled system of the Boussinesq kind, with a reduced number of controls. In the state system, the unknowns are: the velocity field and pressure of the fluid (y, p), the temperature θ and an additional variable c that can be viewed as the concentration of a contaminant solute. We prove several results, that essentially show that it is sufficient to act locally in space on the equations satisfied by θ and c.